The Native Structure and Composition of the Cruciferin Complex in Brassica napus - Nietzel, Thomas (American Society for Biochemistry and Molecular Biology, 2013)
Globulins are an important group of seed storage proteins in dicotyledonous plants. They are synthesized during seed development, assembled into very compact protein complexes, and finally stored in protein storage vacuoles (PSVs). Here, we report a proteomic investigation on the native composition and structure of cruciferin, the 12 S globulin of Brassica napus. PSVs were directly purified from mature seeds by differential centrifugations. Upon analyses by blue native (BN) PAGE, two major types of cruciferin complexes of ∼ 300–390 kDa and of ∼470 kDa are resolved. Analyses by two-dimensional BN/SDS-PAGE revealed that both types of complexes are composed of several copies of the cruciferin α and β polypeptide chains, which are present in various isoforms. Protein analyses by two-dimensional isoelectric focusing (IEF)/SDS-PAGE not only revealed different α and β isoforms but also several further versions of the two polypeptide chains that most likely differ with respect to posttranslational modifications. Overall, more than 30 distinct forms of cruciferin were identified by mass spectrometry. To obtain insights into the structure of the cruciferin holocomplex, a native PSV fraction was analyzed by single particle electron microscopy. More than 20,000 images were collected, classified, and used for the calculation of detailed projection maps of the complex. In contrast to previous reports on globulin structure in other plant species, the cruciferin complex of Brassica napus has an octameric barrel-like structure, which represents a very compact building block optimized for maximal storage of amino acids within minimal space.